2015
DOI: 10.1101/gad.261271.115
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of human global and transcription-coupled excision repair of UV damage at single-nucleotide resolution

Abstract: We developed a method for genome-wide mapping of DNA excision repair named XR-seq (excision repair sequencing). Human nucleotide excision repair generates two incisions surrounding the site of damage, creating an ∼30-mer. In XR-seq, this fragment is isolated and subjected to high-throughput sequencing. We used XR-seq to produce stranded, nucleotide-resolution maps of repair of two UV-induced DNA damages in human cells: cyclobutane pyrimidine dimers (CPDs) and (6-4) pyrimidine-pyrimidone photoproducts [(6-4)PPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

39
362
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 231 publications
(421 citation statements)
references
References 66 publications
(91 reference statements)
39
362
0
Order By: Relevance
“…Previous genomic studies have suggested that NER activity is affected by chromatin state and inhibited by transcription factor binding (7)(8)(9)(10). However, it is not known how these and other features of the chromosomal landscape affect initial UV damage formation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous genomic studies have suggested that NER activity is affected by chromatin state and inhibited by transcription factor binding (7)(8)(9)(10). However, it is not known how these and other features of the chromosomal landscape affect initial UV damage formation.…”
Section: Discussionmentioning
confidence: 95%
“…In these studies, a high-throughput sequencing method, known as excision repair-sequencing (XR-seq), was used to analyze oligonucleotide fragments excised during NER of CPDs or 6-4PPs. These studies found increased repair activity associated with TC-NER of the TS of actively expressed genes and noncoding transcripts (7,8). There was also more rapid repair in active chromatin domains (i.e., enhancers and promoters) and DNase I hypersensitivity regions, and slower repair associated with repressed and heterochromatin regions (8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A genome-wide comparison of open chromatin status, histone modifications, RNA expression, and DNA damage and repair would allow inference of how these processes are coordinated. We recently developed an assay for mapping DNA excision repair at nucleotide resolution across the human genome called eXcision Repair sequencing (XR-seq) (11). In XR-seq, the excised oligonucleotides, released during repair in vivo, are isolated and sequenced, resulting in a stranded, single-nucleotide resolution map of repair (Fig.…”
mentioning
confidence: 99%